Aktualisasi ‘Kemalik’ sebagai Dokumen Hukum Kearifan Lokal Masyarakat Adat Sade dalam Penegakan Hukum Lingkungan - Yulias Erwin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Environmental protection requires robust legal instruments grounded in sound philosophical principles. While environmental laws must be carefully formulated and enforced, their implementation often overlooks the significance of customary law and local knowledge. Existing studies have primarily focused on statutory environmental regulations but have not sufficiently examined the role of customary legal frameworks, such as Kemalik in the Sade Indigenous Community, in environmental conservation. This study investigates how the Sade people in Rambitan Village, Pujut Subdistrict, Central Lombok Regency, West Nusa Tenggara Province, utilize Kemalik as a customary legal system for environmental protection. A normative-empirical legal analysis was employed, combining a review of environmental laws with an empirical field investigation. The normative approach examines existing environmental regulations, while the empirical method involves in-depth interviews with indigenous leaders to assess the practical implementation and effectiveness of Kemalik in environmental stewardship. The findings indicate that Kemalik is not formally integrated into official environmental legislation despite its cultural and ecological significance. This legal disconnect reduces its effectiveness in preventing and mitigating environmental degradation, particularly in the Kiyangan customary forest. Moreover, most local government programs fail to incorporate indigenous environmental values, resulting in ineffective conservation outcomes. This study highlights the need to integrate customary and statutory legal frameworks to enhance environmental governance. It advocates for formally recognizing and incorporating indigenous knowledge into national environmental policies, fostering a more inclusive and comprehensive legal framework for sustainable environmental management.